Diseño de una solución que permita aumentar la eficiencia del protocolo de registro de ingreso y salida de usuarios pediátricos a la FVL. (2020)
Purpose - Security is an indispensable value for any service provider institution. Hotels, supermarkets, insurers, banks, schools, universities, hospitals, among others, must ensure the well-being of their users, and this is why each of them has implemented different strategies to achieve this. This is the case of the Valle de Lili Foundation (FVL), located in the city of Cali, Colombia, which is committed to this purpose, generating an entry and exit registration protocol for pediatric users, that is, this institution has special interest, in making sure that their facilities do not represent any risk for the little ones. However, this process is not developed optimally, therefore, the risk of abduction or loss of minors persists and, furthermore, it is compromising the well-being of other users and the dynamics among the actors involved, being these parents family or responsible and security personnel. In this way, it was found that Interactive Media is a bridge to create new strategies that, focused on the user, can improve the experience of security personnel, children, their caregivers and the foundation itself, and also develop a solution innovative that allows the institution to be more efficient in the process and guarantee greater security. Design/methodology/approach - The project was carried out following the double diamond model of the “British Design Council” which has 4 stages. In the first stage, it was investigated what was the world panorama around the abduction of minors, transnational crime, human trafficking, and the consequences that would affect the FVL if the entry and exit registration protocol would fail. In the second stage, all the information collected in the field work was analyzed and the main pains were identified around the entry and exit registration protocol. In the fourth stage, the development of the prototype was made. Finally, there is the fourth stage, which was implementation.